CFD analysis of heat transfer enhancement in plate-fin heat sinks with fillet profile: Investigation of new designs. (1st June 2020) - Freegah, Basim; Hussain, Ammar A.; Falih, Abeer H.; Towsyfyan, Hossein
Abstract: In the last decades, attempts have been made on developing more advanced effective cooling technologies of electronic and microelectronic equipment, however, the heat dissipation is still the main challenge for enhancing the cooling efficiency of heat sinks in a highly competitive electronic industry. In current study, the investigation develops a new thermal design for plate-fin heat sinks with fillet profile so that the removed material from the base, to generate fillet, is attached to the plate-fins in the form of half-round pins. To evaluation of thermal performance of the proposed designs, a numerical study has been carried out based on commercially available computational fluid dynamic (CFD) codes. In particular, different arrangements of half-round pins (which are attached to the plate-fins) subject to both parallel and impinging flow have been compared in terms of their thermal efficiency. The study has shown that the plate-fin heat sinks with corrugated half-round pins in vertical arrangement subject to parallel flow and plate-fin heat sinks with symmetrical half-round hollow pins in vertical arrangement subject to impinging flow show superior thermal performance over other configurations. The former design provides approximately 25.1% and 29% reduction in the base temperature and thermal resistance respectively along with approximately 34.48% increase in Nusselt number rather than the conventional plate-fins with fillet profile. For the latter design, approximately 22.6% and 25.7% reduction in the base temperature and thermal resistance were achieved respectively while Nusselt number sees approximately 31.6% higher values. Therefore, these designs have a promising potential to be applied for cooling the electronic devices.